Spatial Patterns and Road Network Accessibility of Cultural Heritage for Tourism Potentials in Banswara District, Rajasthan (India) - Dave, Viranch N.; Mankad, Mudit D. (Turizam, 2025)
ABSTRACTIntegrating cultural heritage with tourism helps reveal the tangible and intangible characteristics of a place that are the outcome of long-term interactions between the local population and their natural environment. The goal of this study is to investigate cultural heritage in relation to the tourism development in Banswara district, Rajasthan, India. The study first identified and classified the cultural heritage sites of Banswara district; thereafter, it used spatial statistics tools from ArcGIS 10.7 to find out distribution patterns as well as clusters and hotspots of cultural heritage. In addition to this, accessibility to cultural heritage sites is examined using buffer analysis. The results derived show the presence of hotspots and coldspots in the central part of Banswara district, which includes the Talwara Block. Compared to intangible cultural heritage, which is more sporadic, tangible cultural heritage tends to form hotspots and exhibits a more clustered pattern. Also, tangible cultural heritage sites are frequently found close to major highways when compared to intangible cultural heritage. This research can help planners formulate different strategies for incorporating cultural heritage for tourism development, and it can also help in the revitalization of those aspects of culture that face extinction.
Keywords: Cultural Heritage, Intangible, Tangible, Tourism, Accessibility, Spatial autocorrelation